A Novel Porous Diamond - Titanium Biomaterial: Structure, Microstructure, Physico-Mechanical Properties and Biocompatibility - GUIMARÃES,ZULMIRA A.S. (2017)
ABSTRACT With the aim of introducing permanent prostheses with main properties equivalent to cortical human bone, Ti-diamond composites were processed through powder metallurgy. Grade 1 titanium and mixtures of Ti powder with 2%, 5% and 10 wt% diamond were compacted at 100MPa, and then sintered at 1250°C/2hr/10-6mbar. Sintered samples were studied in the point of view of their microstructures, structures, yield strength and elastic modulus. The results showed that the best addition of diamonds was 2 wt%, which led to a uniform porosity, yield strength of 370MPa and elastic modulus of 13.9 GPa. Samples of Ti and Ti-2% diamond were subjected to in vitro cytotoxicity test, using cultures of VERO cells, and it resulted in a biocompatible and nontoxic composite material.